An Indian Tantric Tradition and Its Modern Global Revival: Contemporary Nondual Śaivism, 1st edition - Osto, Douglas (Routledge, 2020)
This book analyzes the contemporary global revival of Nondual Śaivism, a thousand-year-old medieval Hindu religious philosophy. Providing a historical overview of the seminal people and groups responsible for the revival, the book compares the tradition’s medieval Indian origins to modern forms, which are situated within distinctively contemporary religious, economic and technological contexts.